Efect of pH on Growth, Spore Production and Spore Viability of Biocontrol Agent Trichoderma Harzianum in Submerger Fermentation - Said, Syahiddin Dahlanr; Hasan, Masitah; Romachandran, KB (ASEAN Journal of Chemical Engineering, 2003)
The effect of pH medium on growth, spore production and spore viability of bicontrol agent Trichoderma harzianum were investigated in a batch farmenter in the range of 4 to 7. The biomass concentration of this fungus at pH 4,6 and uncontrolled pH were higher than at pH 5 and 7 after 18h incubation. The spore produced by the fungus at 6,7 and uncotrolled pH was higher than others. the highest level of spore production (6.67x107 spores/ml) occured at unctrolled pH, but the spore produced in the culture grown at 7 has a higher viability (52,5%) compared to those grown at other pH.